Niezdolność do podjęcia istotnych obowiązków małżeńskich z przyczyn natury psychicznej (kan. 1095, n. 3 KPK) w świetle wyroku Roty Rzymskiej c. Stankiewicz z dnia 27 lipca 2010 r. - Góralski, Wojciech (Ius Matrimoniale, 2017)
The author presents and provides a commentary on the judgment of the Roman Rota, passed on 27.07.2010 (in the third instance) by a panel of auditors coram Stankiewicz in a nullitatis matrimonii case on account on a man’s inability to take up significant conjugal obligations as a result of mental problems (in the first instance a judgment declaring the marriage null and void had been passed, but it was reversed in the second instance); the marriage between the parties, which produced a child, lasted almost eight years. The obtained evidence (testimonies of parties and witnesses, two opinions of experts, obtained in the first and third instance) enabled judges of the third instance to assume that the man’s (the defendant’s) inability to take up significant conjugal obligations has not been proven. It has been concluded that his passivity and dependence on his parents was not pathological in nature.